The Metabolic Score for Visceral Fat (METS-VF) as a predictor of diabetes mellitus: Evidence from the 2011-2018 NHANES study. - Harshita Tripathi; Amandeep Singh; Farheen; Bindu Prakash; Dharmendra Kumar Dubey; Prayas Sethi; Ranveer Singh Jadon; Piyush Ranjan; Naval K Vikram (PLoS ONE)
Introduction With 42.4% of obese US population, the prevalence of diabetes mellitus (DM) is increasing. Visceral fat, even at the same body mass index, has significant deleterious effects. This study aims to investigate the association between the Metabolic Score for Visceral Fat (METS-VF) and DM. Methods The study utilized data from NHANES dataset, covering cycles from 2011 to 2018. Multivariate logistic regression and Receiver Operating Characteristic (ROC) analysis assessed the association between METS-VF and DM. Additionally, the study compared visceral adipose tissue (VAT) measurement indices to METS-VF for the prediction of DM. Results In 3,445 participants, METS-VF was positively associated with diabetes [(OR 6.8; 95% CI 5.3-8.6) (AUC 0.791; 95% CI 0.768-0.814)], the association increased across quartiles (METS-VF >6.5; OR 53.8; 95% CI 0.17-169).METS-VF significantly identifies diabetes compared to other VAT indices (LAP, VAI, waist circumference, and WHtR). Additionally premenopausal females with BMI >25 and METS-VF >6.5 are at a higher risk of developing diabetes. Conclusion METS-VF positively associates with the prevalence of diabetes. It is an effective score compared to surrogate markers for VAT measurement. Routine screening of VAT using METS-VF score could be implemented in daily clinical settings and large-scale epidemiological studies to help identify early diabetes.